Multiphase PCL semi-interpenetrating networks exhibiting the triple- and stress-free two-way shape memory effect. Issue 13 (8th March 2023) - Uto, Koichiro; Matsushita, Yoshitaka; Ebara, Mitsuhiro
Abstract : The development of multiphase polymer networks by semi-IPNs composed of homologous polymers using poly(ε-caprolactone). Abstract : Multiple- and two-way shape memory polymers (SMPs) are of great interest in the fields of biomedical devices, smart actuators, and soft robotics owing to their ability to achieve complex movements in response to external stimuli. The formation of multiphase polymer networks exhibiting multiple transition temperatures is a versatile design strategy for achieving the multi- or two-way shape memory effect (SME); however, most of them are combinations of heterogeneous polymers, and no system has achieved them using a material composed of only homogeneous polymers. In this study, multiphasic semi-interpenetrating polymer networks (IPNs) with linear poly(ε-caprolactone) (PCL) chains were designed, which are interpenetrated into the crosslinked PCL network and not involved in crosslinking. Furthermore, the effects of the molecular weight and content of linear PCL chains in the semi-IPNs on crystallisation and melting were investigated. While crosslinked PCL exhibits a monophasic and sharp phase transition, the presence of linear PCLs influences the crystallisation/melting behaviour of other chains and determines the broadening of transition and appearance of an additional transition. Thermal, crystal structure, and thermomechanical characterisation revealed that PCL semi-IPNs composed of linear PCLs with a high molecular weight ( M n  = 80k) and content (>23 wt%) form distinctly separated crystalline phases and undergoes two-phase melting and crystallisation. As expected, these multiphase PCL semi-IPNs can exhibit triple- and two-way SMEs, opening new avenues for the synthesis and design strategies for multiphase polymer networks of semi-IPNs composed of homologous polymers.